SERUM INHIBIN B AS A DIAGNOSTIC MARKER OF MALE INFERTILITY - Manzoor, Syed Mohsin; Sattar, Abdus; Hashim, Rizwan; Khan, Farooq Ahmad; Younas, Muhammad; Ali, Asif; Dilawar, Muhammad; Ijaz, Amir (Journal of Ayub Medical College Abbottabad, 2012)
Background: Infertility affects about 15% of all couples in the world. Approximately 40% of all infertility cases could be attributed entirely to male factors. Serum inhibin B has emerged as a sensitive marker of male fertility. Analysis of serum inhibin B reflects the relationship between inhibin B, Sertoli cell function and spermatogenesis. Methods: This validation study was conducted to calculate the sensitivity, specificity, positive and negative predictive value of serum inhibin B in diagnosis of male infertility, using semen analysis as the gold standard. One hundred and sixty men were included in the study, they reported for semen analysis for evaluation of male infertility. Sperm count was done per standard procedure. Serum inhibin B level was determined by ELISA. Results: Serum inhibin B level ï‚³80 Ïg/ml was regarded as a normal response. The serum inhibin B test had 75% sensitivity, 93.1% specificity, 80.5% PPV and 90.7% NPV. Conclusion: Serum inhibin B has a positive correlation with sperm counts and could be used for evaluation of male infertility as a non-invasive predictor of spermatogenesis. The sensitivity, specificity and PPV are appropriate for clinical decision making and to avoid unnecessary testicular biopsies. Keywords: Inhibin B, male infertility, sensitivity, specificity, predictive values